2009
DOI: 10.1093/ije/dyp286
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to indoor biomass fuel and tobacco smoke and risk of adverse reproductive outcomes, mortality, respiratory morbidity and growth among newborn infants in south India

Abstract: Open burning of biomass fuel in the home is associated with significant health risks to the newborn child and young infant. Community-based trials are needed to clarify causal connections and identify effective approaches to reduce this burden of illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 28 publications
12
138
2
Order By: Relevance
“…This is of great health significance. For example, indoor use biomass fuel is associated with tuberculosis (Pokhrel et al, 2010) risk of low birth weight and stillbirth (Pope et al, 2010), adverse reproductive outcomes, mortality and respiratory morbidity (Tielsch et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…This is of great health significance. For example, indoor use biomass fuel is associated with tuberculosis (Pokhrel et al, 2010) risk of low birth weight and stillbirth (Pope et al, 2010), adverse reproductive outcomes, mortality and respiratory morbidity (Tielsch et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…[5,10,11] Because of falling fertility rates in industrialized societies, [12][13][14] there is a growing awareness that parental exposures to occupational hazards affect fetal development. [15][16][17][18] Due to these circumstances, modern workplace shift work exposure surveys focusing simultaneously on childbearing and birth weight are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are caused by impairment of lung function due to physicochemical properties of the inhaled particles (Schwarze et al 2006). Population based studies have shown an increased risk of low birth weight associated with households that use biomass fuel (Boy et al 2002;Siddiqui et al 2008;Tielsch et al 2009;Thompson et al 2011). In these studies exposure to biomass fuel smoke is chronic (on a daily basis) while forest fires are seasonal.…”
Section: Resultsmentioning
confidence: 99%